Studies over Asteraceae from the restingas on the coast of Pará state, Amazonia, Brazil: Estudios sobre Asteraceae de restingas en la costa del estado de Pará, Amazonía, Brasil (Research, Society and Development, 2022)
The Pará’s restingas are constituted for environments formed by abiotic and biotic components, in coastal areas, where plant communities stand out. Research to learn about the region's plant diversity is essential to help in your preservation. Thus, the botanic family Asteraceae Berchtold & J. Presl is the aim of this study. From this study it was observed that the group is represented in the local for 10 species: Acanthospermum australe (Loefl.) Kuntze, Ambrosia microcephala DC., Eclipta prostrata (L.) L., Emilia sonchifolia (L.) DC., Ichthyothere terminalis (Spreng.) S.F.Blake, Lepidaploa arenaria (Mart. ex DC.) H.Rob., Mikania congesta DC., Rolandra fruticosa (L.) Kuntze, Sphagneticola trilobata (L.) Pruski and Tilesia baccata (L.) Pruski. Therefore, the present scientific work carries out the study of Asteraceae in the restingas from the coast of Pará state, through morphological descriptions, taxonomic comments, scientific illustrations, and an analytical key for species identification. Aiming to assist in the knowledge of this important plant group, as well as its characteristics and particularities, in order to contribute to its preservation.